101-6x=39x+16

Simple and best practice solution for 101-6x=39x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 101-6x=39x+16 equation:


Simplifying
101 + -6x = 39x + 16

Reorder the terms:
101 + -6x = 16 + 39x

Solving
101 + -6x = 16 + 39x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-39x' to each side of the equation.
101 + -6x + -39x = 16 + 39x + -39x

Combine like terms: -6x + -39x = -45x
101 + -45x = 16 + 39x + -39x

Combine like terms: 39x + -39x = 0
101 + -45x = 16 + 0
101 + -45x = 16

Add '-101' to each side of the equation.
101 + -101 + -45x = 16 + -101

Combine like terms: 101 + -101 = 0
0 + -45x = 16 + -101
-45x = 16 + -101

Combine like terms: 16 + -101 = -85
-45x = -85

Divide each side by '-45'.
x = 1.888888889

Simplifying
x = 1.888888889

See similar equations:

| 7+c=13 | | 11(x+3)=4(3x-4) | | 4x^2-19x+20=4x+5 | | 46-2x=8 | | 6x+6=122-10x | | 11x+3=4(3x+4) | | -x^5-x^3+4x=0 | | 11x+3=4x(3x+4) | | -49-7x=9x+17 | | D-8=12 | | 20=3w-1 | | 4k-9k=10j | | 12x(3x-3)-6x(7x-9)= | | 4(2x+3)=7x+4 | | B(b-7)= | | x^2+18x+19=8x-5 | | 4(10d-4)=64 | | x^2+4x+9=6 | | 10(d-4)=60 | | 3x+2x=4x-8 | | 5(3x+3)=30 | | 2(2m-1)=18 | | 5(m-1)=30 | | 3(5a+2)=36 | | 4(2x)-(x+5)= | | 11u-88=3u | | 3(4x-1)=21 | | 0.5(9x+18)=-1.5(5x)-2(3x+4.5) | | 3x^3+26x^2+35x=0 | | 7w=5w+16 | | 3(3y+5)=5y+25 | | graphy=7+10x |

Equations solver categories